دراسة سريرية مقارنة بين الجسور الخزفية- المعدنية والجسور الخزفية الخالية من المعدن (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من هذه الدراسة هو الحصول على معلومات سريريه مقارنه  عن مزايا ومساوئ كل من التعويضات السيراميكية- المعدنية والتعويضات السيراميكية- الخالية من المعدن . تم  إجراء التعويضات السيراميكية الخالية من المعدن  من نظام  IN-CERAM  والتعويضات السيراميكية المعدنية من نظام  OMEGA 900  من شركة      VITA الألمانية لكل من المرضى الذين اختيروا لهذا البحث وعددهم /50/  مريضا وبعد مراقبة حالاتهم الفموية والسنية لمدة/ 3/ سنوات  وتقييم هذه التعويضات من حيث : 1- ردود الفعل اللثوية . 2- الخصائص التجميلية تحت ظروف الإضاءة المختلفة . 3 -المتطلبات  التقنية لهذه التعويضات عند التحضير 4-  فشل هذه التعويضات جزئيا أو كليا. تم جمع المعلومات الخاصة بكل مريض على استمارة مصممة بشكل خاص يمكن إدخال مضمونها إلى البرنامج الإحصائي SPSS   الذي استخدمت منه النسخة/ 11/  VERSION وبإجراء التحليل NON PARAMATRIC TEST تم الحصول على المعلومات الإحصائية التي تفيد بأفضلية التعويضات السيراميكية الخالية من المعدن من النواحي التالية : 1-العلاقة  مع النسج ما حول السنية .الصحية والتجميلية . 2-المظهر التجميلي للتعويض ذاته  تحت  الأنواع المختلفة من الأضواء . أما من حيث الخصائص الأخرى فلم نجد بالدراسة الإحصائية اختلافات ذات دلاله وهذه الخصائص هي : 1-الحاجة لاستئصال الباب الأسنان بسبب التحضير . 2-الحاجة لتقوية الأسنان الداعمة بالاوتاد والقلوب بسبب التحضير : 3-فشل التعويض الجزئي أو الكامل ضمن فترة الدراسة . من هذه النتائج ننصح باستخدام الجسور السيراميكية الخالية من المعدن في حالات  التتويج الإفرادي وحالات الجسور الثابتة –الثابتة لما لها من مزايا إضافية على الجسور السيراميكية المعدنية. The aim of  this research  is getting  clinical information   comparing  between  advantages of  Metal- Ceramic bridges & Metal –free ceramic bridges  and their disadvantages . The partially missing teeth of   /50/ patients    were  replaced by these two systems of ceramic prostheses ; Omega/900/ & In-ceram , from VITA co.  for every  patient. Their mouths cases were watched for three years from points: 1-  Periodontal tissues responses. 2-Esthitc properties under different kinds of light. 3- Clinical  requirements of  installing each  system. 4- Partial or complete failure of each system . The results of checking up of the mouths  cases were collected by a special designed  forms . then these results  were analysisd  by SPSS program version /11/ for evaluating the  important of the statistical differences .The statistical tests  - non parametric test- refereed to: 1-The differences between the two types of bridges were significant statistically from the  points : A- There were positive responses of periodontal tissues toward  In- ceram  bridges. Whereas Metal –ceramic bridges had many negative reaction. B-Esthetic properties of In-ceram  bridges  under deferent types of light .whereas the appearance of metal-ceramic bridges defers according to surrounding   light 2- There weren't significant differences between the two types of bridges from points:  A-The need to indodontic treatments B-The need to strengthen the abutments by post and core. C-Rate of partial ore complete mechanical failures of the two  types of bridges .   So ,we can conclude : that dentists can avoid  esthetic & gingival   negative response by using   the in-ceram bridges instead of  metal-ceramic bridges .without any confusion about  its others  properties